2005
DOI: 10.1300/j179v04n03_04
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internet-Based Electronic Marketplaces on Buyer-Supplier Relationships

Abstract: This paper explores the impact of electronic marketplaces (EMs) on buyer-supplier relationships using a case study approach. Three aspects were investigated: economic benefits, structural changes, and participant satisfaction. Contrary to the literature that treats the emergence of EMs as evidence of "moving towards markets," we first confirmed that EMs benefit both long-term and short-term relationships. They are separate entities that can cause structural changes in the direction of either markets or hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…It is suggested from a disconfirmation of expectations perspective (Churchill and Superant, 1982) that the product/market characteristics suggested by TCT models, as well as company size and prior experience with EMs, have little direct impact on goal setting for EM type choice. In fact, a variety of marketing literature (Clark, 2000) and EM literature (Wang, Archer and Zheng, 2005 and Christainaase and Markus, 2003) suggests instead that formal and informal management expectations are more strongly driven by management perceptions of fit with the broad internal and external environments of the firm.…”
Section: Firstly Confirmatory Factor Analysis Demonstrated Performanmentioning
confidence: 99%
See 4 more Smart Citations
“…It is suggested from a disconfirmation of expectations perspective (Churchill and Superant, 1982) that the product/market characteristics suggested by TCT models, as well as company size and prior experience with EMs, have little direct impact on goal setting for EM type choice. In fact, a variety of marketing literature (Clark, 2000) and EM literature (Wang, Archer and Zheng, 2005 and Christainaase and Markus, 2003) suggests instead that formal and informal management expectations are more strongly driven by management perceptions of fit with the broad internal and external environments of the firm.…”
Section: Firstly Confirmatory Factor Analysis Demonstrated Performanmentioning
confidence: 99%
“…Transaction cost theory (TCT) has contributed to understanding of the matching of product-market characteristics to the type of EM employed via numerous prescriptive models (Malone et al 1987;Bakos, 1991 andMahadevan, 2003). In addition, recent literature has indicated that company size (Hadaya, 2004), prior experience (Hadaya, 2004;Corbitt, 2003), and role (buyer or seller) (Rask and Kragh, 2004;Wang, Archer and Zheng, 2005) all impact marketers' perceptions of performance for electronic marketplaces once they have been adopted.…”
Section: Firstly Confirmatory Factor Analysis Demonstrated Performanmentioning
confidence: 99%
See 3 more Smart Citations